Validating activity indices from camera traps for commensal rodents and other wildlife in and around farm buildings. Issue 1 (27th September 2017) - Lambert, Mark; Bellamy, Fiona; Budgey, Richard; Callaby, Rebecca; Coats, Julia; Talling, Janet
Abstract : Activity indices for commensal rodents are required for rodenticide efficacy evaluation. Here we validate a method using camera traps to derive passive activity indices for Norway rats and house mice. Abstract: BACKGROUND: Indices of rodent activity are used as indicators of population change during field evaluation of rodenticides. We investigated the potential for using camera traps to determine activity indices for commensal rodents living in and around farm buildings, and sought to compare these indices against previously calibrated survey methods. RESULTS: We recorded 41 263 images of 23 species, including Norway rats ( Rattus norvegicus Berk.) and house mice ( Mus musculus L.). We found a positive correlation between activity indices from camera traps and activity indices from a method (footprint tracking) previously shown to have a linear relationship with population size for Norway rats. Filtering the camera trap data to simulate a 30‐s delay between camera trigger events removed 59.9% of data and did not adversely affect the correlation between activity indices from camera traps and footprint tracking. The relationship between activity indices from footprint tracking and Norway rat population size is known from a previous study; from this, we determined the relationship between activity indices from camera traps and population size for Norway rats living in and around farm buildings. CONCLUSION: Systematic use of camera traps was used to determine activity indices for Norway rats living in and around farm buildings; the activity indices were positively correlated with those derived from a method previously calibrated against known population size for this species in this context. © 2017 Crown copyright. Pest Management Science © 2017 Society of Chemical Industry